2009
DOI: 10.1021/cm902199p
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Growth and Magnetic Property of FePt Nanostructure: Cuboctahedron, Octapod, Truncated Cube, and Cube

Abstract: The strategy for shape control of alloy FePt nanocrystal was studied systematically. By the careful adjustments of reaction parameters in a solution reaction, surfactant-facet bindings on the growth seed were controlled delicately. FePt octapod, cuboctahedron, truncated cube, and nanocube were successfully prepared from cuboctahedral seed and examined by high-resolution transmission electron microscopy. The formations of FePt nanostructures were mainly attributed to the differences in the growth rate between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(84 citation statements)
references
References 45 publications
3
76
1
Order By: Relevance
“…To ensure the formation of PtIr nanocubes, certain binding agents should be introduced to make the total surface energy of (100) crystal facets to be the lowest so as to facilitate the elimination of other planes during the growth. Although it has been widely reported that the amine group of oleylamine tends to bind on the Pt (100) planes rather than on the (111) planes [50,51], the results from the present work clearly demonstrates that oleylamine alone is not be able to stabilized the Pt (100) planes (Fig. 2a).…”
Section: Resultscontrasting
confidence: 74%
See 3 more Smart Citations
“…To ensure the formation of PtIr nanocubes, certain binding agents should be introduced to make the total surface energy of (100) crystal facets to be the lowest so as to facilitate the elimination of other planes during the growth. Although it has been widely reported that the amine group of oleylamine tends to bind on the Pt (100) planes rather than on the (111) planes [50,51], the results from the present work clearly demonstrates that oleylamine alone is not be able to stabilized the Pt (100) planes (Fig. 2a).…”
Section: Resultscontrasting
confidence: 74%
“…Most of the Pt-Ir NPs exhibit a hexagonal shape with an average particle size of 6.5 ± 0.6 nm, with a small mixture of irregular-shaped NPs. The actual shape of the Pt-Ir NPs may be cuboctahedral that matches the hexagonal projection observed in the TEM image [50]. Oleylamine and oleic acid have different functional head groups, i.e., amine group for oleylamine instead of carboxyl group for oleic acid.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…25 The TEM images showed no agglomeration, which suggests the excellent monodispersity of FePt NPs because of two reasons: 1) a low reaction temperature (40°C), and 2) the negatively-charged surface resulting in the interparticle repulsive force. 35 Figure 1D shows that the saturated mass magnetization of FePt NPs was 1.13 emu/g, coupled with the absence of coercive force, which indicated that the FePt NPs exhibited superparamagnetic behavior at 300 K. 36 The ligand exchange was confirmed by FTIR measurements in the range of 400-4,000 cm -1 with 2 cm -1 resolution at room temperature. The recorded spectrums of bare FePt NPs, Cys, and Cys-capped FePt NPs are shown in Figure 1E.…”
Section: Mri and Ct Imaging In Vitromentioning
confidence: 90%